Identitas Keindonesiaan dan Aktualisasi Pancasila bagi Generasi Milenial di Era Digital - Yudi Latif (Lembaga Ketahanan Nasional Republik Indonesia, 2018)
The conception of the nation-state rests with the subject of formative experience round up to the declaration of independence and its subsequent institution of governance. This experience is shaped by the best mind of the nation –in most account by their intelligentsia. In their youth, the generation of intelligentsia transform their situation into what can be ethically said about their statement in the world, since they are determined to change their society. Indonesia has a generation of intelligentsia who later became the founder of the nation and the framer of normative norm and common ground, Pancasila. Their youth informed us on the foundation and values of Indonesia. In the contemporary of Indonesia, the youth of diverse background has been searching for what their society stands for, much likes the generation of pre-independence Indonesia. Their role too still search for spaces and trajectory where they can espouse their lead and claim on the actualisation of Pancasila. Those, as it is turned out, would not be an easy one since the landscape of nationhood has various challenges waiting to be defined by them.